Large pancreatic lipoma in a 69-year-old diabetic woman: diagnostic considerations - Budzyńska, Agnieszka; Nowakowska-Duława, Ewa; Cholewka, Andrzej; Pilch-Kowalczyk, Joanna; Kajor, Maciej (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Pancreatic mesenchymal neoplasms are very rare pancreatic tumours. One of them is pancreatic lipoma, often diagnosed incidentally. We herein report a case of a large lipoma of the pancreatic head, diagnosed by computed tomography and magnetic resonance imaging and confirmed by ultrasound-guided fine needle biopsy (FNA) biopsy. Regarding its benign character, silent clinical course and excellent prognosis of invasive surgical removal was avoided. We propose here the diagnostic and therapeutic management of these rare pancreatic tumours. Computed tomography is the most accurate method to diagnose pancreatic lipoma. Nevertheless large tumours may need confirmation by FNA in differential diagnosis of liposarcoma.